SOCIAL-PHILOSOPHICAL MECHANISMS OF HISTORICAL CONSCIOUSNESS IN STRENGTHENING PATRIOTISM IN YOUTH (TAMADDUN NURI JURNALI, 2024)
This article analyzes the work of a number of researchers on the formation and education of the sense of patriotism, the socio-philosophical mechanisms of historical consciousness in strengthening patriotism among young people.